2009
DOI: 10.1186/1297-9686-41-22
|View full text |Cite
|
Sign up to set email alerts
|

Genetic architecture of trout from Albania as revealed by mtDNA control region variation

Abstract: To determine the genetic architecture of trout in Albania, 87 individuals were collected from 19 riverine and lacustrine sites in Albania, FYROM and Greece. All individuals were analyzed for sequence variation in the mtDNA control region. Among fourteen haplotypes detected, four previously unpublished haplotypes, bearing a close relationship to haplotypes of the Adriatic and marmoratus lineages of Salmo trutta, were revealed. Ten previously described haplotypes, characteristic of S. ohridanus, S. letnica and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 32 publications
2
35
1
Order By: Relevance
“…It should be emphasized that one of the most important factors determining the efficiency of conservation management of endangered fish species is the origin and quality of stocking material. Baseline genetic data are essential during welldeveloped restitution programs, enabling proper identification and selection of stocking material for supplementing wild populations, originating from proper stocks, being characterized by a high level of genetic diversity (Razpet et al 2007;Snoj et al 2009). Therefore, studies on the genetic structure of stock or population are crucial for conservation management of endangered fish species protected by a rehabilitation measure, such as European huchen.…”
Section: Introductionmentioning
confidence: 99%
“…It should be emphasized that one of the most important factors determining the efficiency of conservation management of endangered fish species is the origin and quality of stocking material. Baseline genetic data are essential during welldeveloped restitution programs, enabling proper identification and selection of stocking material for supplementing wild populations, originating from proper stocks, being characterized by a high level of genetic diversity (Razpet et al 2007;Snoj et al 2009). Therefore, studies on the genetic structure of stock or population are crucial for conservation management of endangered fish species protected by a rehabilitation measure, such as European huchen.…”
Section: Introductionmentioning
confidence: 99%
“…Although S. marmoratus and S. trutta are phylogenetically very closely related [18,19] -indeed S. marmoratus is often considered to be a subspecies of S. trutta -the results of our study show perceptible differences in skin structure between these two species, especially regarding the shape and distribution of melanophores. The phenotypic differences between the species are inherited, and therefore the marble color pattern formation can be categorized as an ultimate morphological change as defined by Leclercq et al [3].…”
Section: Discussionmentioning
confidence: 52%
“…Following different approaches and survey in regard to Salmo spp., population with analyses and application of allozymic loci, mitochondrial (mt) DNA and microsatellites, it has been concluded that Balkan area constitute a region where Salmo spp. populations exhibit particularly high levels of genetic variation [1] and [4]. Further to that [5] and [6] with the mtDNA analyses revealed that four of the five major evolutionary lineages identified throughout the species range were present in the region.…”
Section: Introductionmentioning
confidence: 73%